Gut microbiome-mediated bile acid metabolism regulates liver cancer via NKT cells - Ma, Chi; Longerich, Thomas (Science, 2018)
Bile acids and liver cancer - Liver cancer is a leading cause of cancer-related deaths in the United States. The composition of the gut microbiome influences many human diseases, including liver inflammatory disorders. Ma et al. found that commensal gut bacteria can recruit the immune system to control the growth of liver tumors in mice (see the Perspective by Hartmann and Kronenberg). Clostridium species modified bile acids to signal liver sinusoidal endothelial cells to produce the chemokine CXCL16. This recruited natural killer T (NKT) immune cells to perform antitumor surveillance of the liver. Growth of both primary and metastatic cancer was reduced by NKT cell-driven killing. - Science, this issue p. eaan5931; see also p. 858 - Structured Abstract - INTRODUCTIONPrimary liver tumors and liver metastasis currently represent the leading cause of cancer-related deaths. The liver intimately cross-talks with the gut and performs many essential functions related to digestion, metabolism of nutrients, and clearance of bacterial metabolites. Diseased livers are often associated with altered gut bacterial composition, or dysbiosis, and it has been suggested that gut bacterial products contribute to malignant transformation of hepatocytes. The liver is exposed to the gut microbiome through the portal vein and is an immunological organ that is heavily populated by immune cells. Emerging studies have shown that gut commensal bacteria are important regulators of antitumor immunity. Although it has been established that the gut microbiome influences the efficacy of cancer immunotherapy, the role of gut bacteria in antitumor surveillance in the liver is poorly understood. - RATIONALEThe liver is exposed to gut bacterial metabolites and products by way of blood from the intestine, which comprises 70% of the whole liver blood supply. Changes in the gut microbiome may affect immune cell function in the liver, and commensal bacteria can mediate the metabolism of primary into secondary bile acids, which recirculate back into the liver through the enterohepatic circulation. Given that bile acids are known to be involved in liver cancer development, we focused on the role of bile acids in immunosurveillance of tumors growing in the liver. We altered gut bacteria and examined changes of hepatic immune cells and antitumor immunity directed against liver tumors. Uncovering how the gut microbiome uses bile acids to shape immunity to liver cancer may have future therapeutic applications. - RESULTSUsing one primary liver model and three liver metastasis models, we found that altering commensal gut bacteria induced a liver-selective antitumor effect. A selective increase of hepatic CXCR6+ natural killer T (NKT) cells was observed, independent of mouse strain, gender, or presence of liver tumors. The accumulated hepatic NKT cells showed an activated phenotype and produced more interferon-γ upon antigen stimulation. In vivo studies using both antibody-mediated cell depletion and NKT-deficient mice confirmed that NKT cells mediated the inhibition of tumor growth in the liver. Further investigation showed that NKT cell accumulation was regulated by the expression of CXCL16, the solo ligand for CXCR6, on liver sinusoidal endothelial cells, which form the lining of liver capillaries and the first barrier for the blood coming from the gut entering the liver. Primary bile acids increased CXCL16 expression, whereas secondary bile acids showed the opposite effect. Removing gram-positive bacteria by antibiotic treatment with vancomycin, which contains the bacteria mediating primary-to-secondary bile acid conversion, was sufficient to induce hepatic NKT cell accumulation and decrease liver tumor growth. Feeding secondary bile acids or colonization of bile acid-metabolizing bacteria, reversed both NKT cell accumulation and inhibition of liver tumor growth in mice with altered gut commensal bacteria. In nontumor liver tissue from human patients with primary liver cancer, primary bile acid chenodeoxycholic acid (CDCA) levels correlated with CXCL16 expression, whereas an inverse correlation was observed with secondary bile acid glycolithocholate (GLCA), suggesting that the finding may apply to humans. - CONCLUSIONWe describe a mechanism by which the gut microbiome uses bile acids as messengers to control a chemokine-dependent accumulation of hepatic NKT cells and antitumor immunity in the liver, against both primary and metastatic liver tumors. These findings not only have possible implications for future cancer therapeutic studies but also provide a link between the gut microbiome, its metabolites, and immune responses in the liver. Download high-res image Open in new tab Download Powerpoint Gut microbiome modulates liver cancer through bile acid-regulated NKT cells.Gut microbiome uses bile acids as a messenger to regulate chemokine CXCL16 level on liver sinusoidal endothelial cells (LSEC) and thus controls the accumulation of CXCR6+ hepatic NKT cells. The accumulated NKT cells have an activated phenotype and inhibit liver tumor growth. - Primary liver tumors and liver metastasis currently represent the leading cause of cancer-related death. Commensal bacteria are important regulators of antitumor immunity, and although the liver is exposed to gut bacteria, their role in antitumor surveillance of liver tumors is poorly understood. We found that altering commensal gut bacteria in mice induced a liver-selective antitumor effect, with an increase of hepatic CXCR6+ natural killer T (NKT) cells and heightened interferon-γ production upon antigen stimulation. In vivo functional studies showed that NKT cells mediated liver-selective tumor inhibition. NKT cell accumulation was regulated by CXCL16 expression of liver sinusoidal endothelial cells, which was controlled by gut microbiome-mediated primary-to-secondary bile acid conversion. Our study suggests a link between gut bacteria-controlled bile acid metabolism and liver antitumor immunosurveillance. - Cross-talk between bacteria and bile acid promotes natural killer T cell antitumor immunity in the liver. - Cross-talk between bacteria and bile acid promotes natural killer T cell antitumor immunity in the liver.